Surfactant‐directed Pd‐nanoparticle assemblies as efficient nanoreactors for water remediation - Binbin Huang (EcoMat, 2020)
Abstract Devising new catalytic systems for the efficient removal of organic chlorides from contaminated sites has important benefits for the human health. Efficiency requires the use of performing catalysts and the extraction of the contaminant from the environment. Here we describe a novel strategy that combines both aspects. A one‐pot surfactant‐directed approach allows the preparation of ultrafine palladium nanoparticles (PdNPs) finely dispersed inside well‐ordered geometric structures, ranging from loose vesicles to nanocubes, from cylindrical to spherical assemblies. These assemblies work as nanoreactors where hydrophobic organic chlorides can be concentrated in the surfactant‐tail environment and efficiently reduced by the PdNP catalysts. As a proof‐of‐concept, we studied the dechlorination of the notorious pollutant 4‐chlorophenol. The nanoreactors display rapid dechlorination ability, excellent catalytic activity, and good stability and recyclability. This study provides a new methodology for effective water remediation that combines the advantages of both extraction and supported heterogeneous catalysis.